2020
DOI: 10.1136/tsaco-2019-000396
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive approach to low-velocity penetrating extraperitoneal rectal trauma

Abstract: Unlike intraperitoneal colorectal injuries, the standard of care for extraperitoneal rectal trauma includes a diverting colostomy due to relative inaccessibility of these injuries for primary repair. New technologies to enhance access to the extraperitoneal rectum have gained increasing use in benign and malignant rectal disease. We present two cases of low-velocity penetrating extraperitoneal rectal trauma. In both cases, a transanal minimally invasive surgery (TAMIS) approach was used to access, and primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A recent case report describes the utilization of transanal minimally invasive surgery (TAMIS) to facilitate primary closure of low-velocity penetrating rectal injuries; however, this technique has not yet been widely adopted. 43 While primary repair of rectal injuries and the decision to perform proximal diversion continue to spark debate, there is a relative consensus that both presacral drainage and distal rectal washout are not beneficial to most patients with rectal injuries. While presacral drains were part of the standard management of rectal injuries through the 1980s, the only randomized study published on this issue found higher risk of infectious complications in patients who underwent presacral drainage.…”
Section: Extraperitoneal Rectal Injurymentioning
confidence: 99%
“…A recent case report describes the utilization of transanal minimally invasive surgery (TAMIS) to facilitate primary closure of low-velocity penetrating rectal injuries; however, this technique has not yet been widely adopted. 43 While primary repair of rectal injuries and the decision to perform proximal diversion continue to spark debate, there is a relative consensus that both presacral drainage and distal rectal washout are not beneficial to most patients with rectal injuries. While presacral drains were part of the standard management of rectal injuries through the 1980s, the only randomized study published on this issue found higher risk of infectious complications in patients who underwent presacral drainage.…”
Section: Extraperitoneal Rectal Injurymentioning
confidence: 99%
“…Intraperitoneal rectal lesions are managed in the same way as colonic lesions-that is, they are often treated with direct repair without diversion. In contrast, extraperitoneal rectal lesions are difficult to access and the transabdominal approach only allows the creation of a stoma for fecal diversion [4]. Extraperitoneal rectal lesions can be managed conservatively or surgically, depending on the extent of the lesion.…”
mentioning
confidence: 99%
“…In such cases, the optimization of access to extraperitoneal rectal lesions can allow effective primary repair and avoid the need for diversion. In this context, transanal minimally invasive surgery could increase the likelihood of successful primary repair of extraperitoneal rectal lesions [4]. Mortality rates have declined in recent decades, but despite advances in the management of trauma patients, mortality rates range from 3% to 10%, and the risk of further complications is 18% to 21%.…”
mentioning
confidence: 99%

Anal trauma caused by bull-horn injury

Jara Benedetti,
Maiocchi Segredo,
Martínez Hernández
et al. 2023
Tech Coloproctol